Will Economic Partnership Agreements Increase Poverty? The Case of Uganda. Issue 2 (5th July 2016) - Boysen, Ole; Matthews, Alan
Abstract: Economic Partnership Agreements (EPAs) between the EU and African Caribbean and Pacific countries are frequently criticized because of fears about negative implications for economic development. Using Uganda as a case study, this paper employs an integrated computable general equilibrium‐microsimulation model framework rich in household‐level detail to assess the consequences of the East African Community EPA for economic output and poverty in Uganda. Simulations of the agreement's tariff liberalization provisions indicate a very small negative economic impact and ambiguous outcomes for poverty. The poverty results depend in size and sign on the poverty line, on the way the government addresses tariff revenue losses and on labor market assumptions.